Microscopy Observation of Samosir Formation Paleosoil, Tuktuk Sidaong, North Sumatera, Indonesia. - Danni Gathot Harbowo; Siti Zahra (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
Samosir is the islands that emerge and standing upon on Toba Caldera after it’s the last eruption at 74.000 years ago. Samosir Island known as the caldera floor that uplifts parallel with Toba’s caldera flooding. In this study, we have observed an outcrop in Tumutuk, Samosir Island that hypothesized as a lacustrine deposit, and we found a paleosoil layer that might give more answers about the geological process in this area at the past time. Based on this outcrop, we described it, followed to measure its stratigraphy section, and took representative samples from the paleosoil layer, then observed the samples under the stereo-microscope as polish rock section, in normal light & negative images. As the result we identify several features of paleosoil & its sedimentary grain that shown this paleosoil layer, two events of the volcanoclastic deposits flown, and exposed two-time, and forming soil, it may form in the shallow swamp in a lacustrine environment, coincide with caldera flooding and caldera floor uplift event.